2010
DOI: 10.5120/88-187
|View full text |Cite
|
Sign up to set email alerts
|

A review on Data Mining Applications to the Performance of Stock Marketing

Abstract: Data mining is the extraction of hidden predictive information from large data bases. Data mining is used to increase revenues and reduce costs. Data mining finds patterns and correlations or relationships in data by using sophisticated techniques. In today"s society of high demanding customers, increasing competitiveness and in order to avoid the initial investment of gathering a data without being certain that it will be successful. A customer-focused approach will discover customer"s preferences, needs and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…In general, neural network modeling is among data processing techniques called data mining. Setty et al [24] reviewed the applications of data mining techniques to evaluate the performance of stock markets and concluded that there is a rising gap between storage and retrieval systems. Since storage is more powerful, a technological leap needs to be made to prioritize information about end-user problems.…”
Section: Performances Of Neural Network Modelsmentioning
confidence: 99%
“…In general, neural network modeling is among data processing techniques called data mining. Setty et al [24] reviewed the applications of data mining techniques to evaluate the performance of stock markets and concluded that there is a rising gap between storage and retrieval systems. Since storage is more powerful, a technological leap needs to be made to prioritize information about end-user problems.…”
Section: Performances Of Neural Network Modelsmentioning
confidence: 99%
“…If a company makes profit, then all shareholders get share of this profit according to their percentage of ownership and their stock price goes up. In the same way if the company is in loss then all shareholders have share in loss as well and their stock price goes down ( Setty, Rangaswamy & Subramanya, 2010 ).…”
Section: Key Conceptsmentioning
confidence: 99%
“…Data mining is a method of extracting unknown projecting information from large databases which is a widespread technology that helps organizations to focus on the most important information in data repositories with great potential [7,8,9,10]. Data analysis tools predict future trends and behavior, helping organizations in active business solutions to knowledge driven decisions [6,11,12].…”
Section: Data Miningmentioning
confidence: 99%